On the subject of an ATC simulator exercise in the training of air traffic controllers at Civil Aviation Educational Institutions - R. A. Subbotin (Научный вестник МГТУ ГА)
The task of improving the professional training of air traffic controllers is one of the most important in civil aviation (CA). This is due to the fact that the level of professional training largely determines the level of flight safety and the efficiency of airspace utilization. Updating and technical modernization of ATC systems and aids requires the development of new programs and methodologies for ATCO (ATC officers) training. The methodology of simulator training on the air traffic control simulator, which is a key component of practical training for ATCO in civil aviation educational institutions, also requires continuous improvement. This study analyzes and summarizes the experience of organizing and conducting training exercises on the air traffic control simulator at a university focusing on the phenomenon of exercises on the ATC simulator. The essential features of the exercise were considered: objective, task, aeronautical background, coherence with the training process, type, as well as properties: difficulty and complexity of the exercise. In studying the complexity of the exercise, the concepts of relative and absolute complexity were introduced. The relative complexity of the exercise reflects its external aspect in relation to its place in the structure of the academic discipline and within the system of all the skills being developed. The absolute complexity of the exercise reflects its internal structure as an interconnected set of skills required exclusively for the completion of that specific exercise. Analytical dependencies are proposed for calculating the relative and absolute complexity, taking into account the principle of one complexity. The concepts of practical, average, and individual difficulty of the exercises on the air traffic control simulator are introduced. An analytical dependence for their calculation is proposed. A classification of the exercise on the air traffic control simulator is proposed based on the following criteria: the objectives of the exercise, the form of the exercise, the task being solved in the exercise, the execution time, the degree of instructor involvement, and the form of the comeback from the instructor. Definitions of the concept of the exercise type and, in fact, the very concept of the exercise on the air traffic control simulator are proposed. The results obtained in this work are aimed at further development of theoretical principles in air traffic controllers training and can be used in organizing and conducting simulator practice on the air traffic controller simulator in educational institutions of civil aviation.